Exploring individual differences in photosynthesis and respiration knowledge in the context of green plants - Vančugovienė Vesta; McMullen Jake; Lehtinen Erno; Södervik Ilona (Routledge, Taylor & Francis Group, 2025)
A scientific conceptual understanding of photosynthesis and respiration provides an important basis for understanding nature and the regulations of life. Photosynthesis and respiration are complex processes, and learning about them requires a proper understanding of their various aspects, from molecular biology to the ecosystem level. This study explored conceptual understanding of, and misconceptions about, several fundamental aspects of photosynthesis and respiration. We also examined heterogeneity among students by identifying groups with different patterns of understanding of various aspects of the concepts. In all, 1310 students from the 7th through 11th grades answered 13 two-tier-type questions on various aspects of photosynthesis and respiration. Latent class analysis revealed four unique latent classes: high achievers, low achievers, moderate understanding of photosynthesis with low understanding of respiration, and moderate understanding of photosynthesis with varying understanding of respiration. More than 37% of the participants were assigned to the low achievers class, and less than 10% were assigned to the high achievers class. Respiration was less understood than photosynthesis. There were individual differences in class membership within grade levels; however, all four classes were present in all grade levels.